Pengendalian Isi Dakwah di Rumah Ibadah dan Penguatan Moderasi Beragama bagi Stakeholder di Lombok - Nursyamsu, Nursyamsu; Apipuddin, Apipuddin; Padli , Erwin; Zaenudin Amrulloh4, Zaenudin Amrulloh4 (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2024)
In recent years, repressive, intolerant and conflict-inducing religious practices have developed into several phenomena and trends of religious conflicts in Lombok. The plural and diverse religious patterns of Lombok society are potentials that must be managed well in order to maintain and create a harmonious and tolerant socio-religious life. The face of the community is also the face of the community in Kidang Village. Its tolerant and harmonious religious situation is important to continue to be maintained, considering that the situation has recently been dynamic both in inter-religious and inter-Islamic religious relations which have the potential to trigger conflict. This community service is a workshop activity targeting participants from elements and elements of society such as religious leaders, community leaders, traditional leaders, youth leaders, women, and representatives from houses of worship of three religions, namely Islam, Christianity and Hinduism, totaling 25 people. The purpose of this community service activity is to strengthen religious moderation for stakeholders, form agents for driving religious moderation and develop a mechanism for controlling the content of religious preaching in houses of worship. Community service activities are carried out using lecture and facilitator method.